Case Report: Wernicke's encephalopathy after gastric surgery presenting as lactic acidosis and refractory thrombocytopenia - Lin, Qi; Li, Guanghua; Wang, Zhixiong; Zhang, Yu (Frontiers in Surgery, 2023)
Wernicke's encephalopathy (WE) is a severe neuropsychiatric disorder, which results from a nutritional deficiency of thiamine. WE usually occurs on patients with chronic alcoholism, additionally with the lack of typical symptoms at its early stage. Therefore, non-alcoholic WE patients were often misdiagnosed in many cases. Lactate is an important by-product of anaerobic metabolism when the aerobic metabolism is blocked by the lack of thiamine, which can potentially serve as an alerting index for WE. We report a case of gastric outlet obstruction patient who developed WE after operation, and presented lactic acidosis and refractory thrombocytopenia. A 67-year-old non-alcoholic woman who had suffered 2-month hyperemesis was admitted with gastric outlet obstruction. Gastric biopsies with endoscopy revealed gastric cancer and total gastrectomy together with D2 nodal dissection were performed. She developed in coma rapidly after operation with refractory thrombocytopenia. There was no specific evidence for severe infection and neither her consciousness nor thrombocytopenia was improved by the application of antibiotics. But all these abnormalities got improved after thiamine administration. And we also found her long-term high level of blood lactate before the operation. Early diagnosis for WE is important because delayed diagnosis and intervention can lead to permanent injury to the brain. Even nowadays, the diagnosis for WE mainly depends on clinical symptoms, but typical triad happens quite occasionally among WE patients, for which a sensitive index for early-diagnosis is critical for WE. Blood lactate, which could raise up when thiamine deficiency present, can serve as an alarming factor for WE. Additionally, we noted that a thiamine-sensitive refractory thrombocytopenia happened for this patient, which is not a typical feature for WE. Early diagnosis and timely treatment is extremely important for WE patients. Unexplained high levels of lactate can be an alarming indicator of thiamine deficiency. And at the same time, we noted the thiamine-sensitive refractory thrombocytopenia in this patient, which is not common for WE patient.